Answer:
![{f}^( - 1) (x) = (1)/(x - 1)](https://img.qammunity.org/2021/formulas/mathematics/college/bjcbizvhcl0bax52dcml6kpmp2402i97g6.png)
Option B is the correct option.
Explanation:
Let y = f ( x )
![y = (x + 1)/(x)](https://img.qammunity.org/2021/formulas/mathematics/college/eosbgamqqwofora9k2o0p4vm496r5s0p5p.png)
Apply cross product property
![xy = x + 1](https://img.qammunity.org/2021/formulas/mathematics/college/99h0bwtamcqx78k93nhrrjta0bmuahb2o6.png)
Move 'x' to L.H.S and change it's sign
![xy - x = 1](https://img.qammunity.org/2021/formulas/mathematics/college/mmv4rua1d6900knchx0bb8tfdszt4chfp0.png)
Take x as common
![x(y - 1) = 1](https://img.qammunity.org/2021/formulas/mathematics/college/8vrdy5d6pmtejudmu2ealps0u627y4nttd.png)
![x = (1)/(y - 1)](https://img.qammunity.org/2021/formulas/mathematics/college/w3bo8xwgn1mdxjhfv9j2t3gz3347jlnc6p.png)
Replace x by f ⁻¹(x) and y by x
![{f}^( - 1) (x) = (1)/(x - 1)](https://img.qammunity.org/2021/formulas/mathematics/college/bjcbizvhcl0bax52dcml6kpmp2402i97g6.png)
Hence, Option B is the correct option.
Hope this helps..
Best regards!!